Penerapan Analisis Swot dalam Lembaga Pendidikan Islam - Rini Wahyuni Siregar (Yayasan Rahmat Islamiyah, 2021)
SWOT analysis is part of the strategic planning stage. The organization consists of three stages: the data collection stage, the analysis, and stage of decision making. In the data collection stage can This is done by analyzing the state of the organization both internally and external. Next is to use all this information in strategic formulation models of the school. One of the problem solving models What can be used is swot model.